Amyloid beta accumulations and enhanced neuronal differentiation in cerebral organoids of Dutch-type cerebral amyloid angiopathy patients - Daoutsali, Elena; Pepers, Barry A.; Stamatakis, Stavros; van der Graaf, Linda M.; Terwindt, Gisela M.; Parfitt, David A.; Buijsen, Ronald A. M.; van Roon-Mom, Willeke M. C. (Frontiers in Aging Neuroscience, 2023)
Dutch-type cerebral amyloid angiopathy (D-CAA) is a hereditary brain disorder caused by a point mutation in the amyloid precursor protein (APP) gene. The mutation is located within the amyloid beta (Aβ) domain of APP and leads to accumulation of the Αβ peptide in and around the cerebral vasculature. The lack of disease models to study the cellular and molecular pathological mechanisms of D-CAA together with the absence of a disease phenotype in vitro in overexpression cell models, as well as the limited availability of D-CAA animal models indicates the need for a D-CAA patient-derived model. Using immunofluorescent and targeted gene expression analyses we show that cerebral organoids of D-CAA patients exhibit Aβ accumulations, enhanced neuronal and astrocytic gene expression and TGFβ pathway de-regulation. These results illustrate the potential of cerebral organoids as in vitro disease model that can be used to understand disease mechanisms of D-CAA and serve as therapeutic intervention platform.